2014
DOI: 10.7860/jcdr/2014/7949.4244
|View full text |Cite
|
Sign up to set email alerts
|

Relative Risk of Various Head and Neck Cancers Among Different Blood Groups: An Analytical Study

Abstract: Background: Cancer is a unique disease characterized by abnormal growth of cells which have the ability to invade the adjacent tissues and sometimes even distant organs. The limited and contrasting evidence regarding the association of ABO blood groups with the different types of head and neck cancers in the Indian population warrants the need for the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…However, in the case-control study, we evidenced a significant reduction in the risk of DTC associated with blood group B when compared to blood type O [12]. This association had not been reported before; nevertheless, several studies reveal that there is an inherited element in the susceptibility to or protection against different types of head and neck cancer linked to blood groups [48,49,50]. …”
Section: Discussionmentioning
confidence: 55%
“…However, in the case-control study, we evidenced a significant reduction in the risk of DTC associated with blood group B when compared to blood type O [12]. This association had not been reported before; nevertheless, several studies reveal that there is an inherited element in the susceptibility to or protection against different types of head and neck cancer linked to blood groups [48,49,50]. …”
Section: Discussionmentioning
confidence: 55%
“…Many reports have shown that the ABO blood type system is associated with the development of cancers. Type A has been associated with gastric [ 13 15 ], pancreatic [ 16 19 ], ovarian [ 16 , 20 ], esophageal [ 21 ], salivary gland [ 21 ], and breast cancers [ 16 ], whereas type B has been associated with esophageal [ 22 , 23 ] and laryngeal cancers [ 21 ]. Some reports showed that people with blood type O have lower risks for lung [ 24 ], endometrial [ 25 ], pancreatic [ 26 ], renal cell [ 27 ], and ovarian cancers [ 28 ], and colorectal adenocarcinoma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda, A kan grubu lehine (p <0.001) anlamlı fark olduğu tespit edildi. Literatürde özofagus kanseri ve ABO kan grubu ilişkisi ile ilgili çelişkili sonuçlar olsa da bazı çalışmalar B kan grubu ve A kan grubu ile ilişkilendirilmiştir 30,31 . Bizim çalışmamızda ise özefagus kanseri için anlamlı bir fark bulunamadı.…”
Section: çAlışmaya Dahil Edilen Bireylerdenunclassified